(untitled) (American Journal of Islam and Society, 2009)
With Stolen Honor: Stigmatizing Muslim Men in Berlin, anthropologist Katherine Ewing has made a timely and valuable contribution to the literature on Muslims in Europe. Ewing explores the stigmatization of Muslims of Turkish origin in light of multiple societal controversies ranging from honor killings to citizenship tests meant to determine who can belong to the German nation.While the focus in both the popularmedia and social science literature has typically been on Muslim women in western societies, Stolen Honor offers a novel perspective on men, who are usually overlooked by social scientists and demonized by the media ...